A Novel Commence For Optimizing Task Scheduling In Heterogeneous Multiprocessor Environment Using Genetic Algorithm - Rani, Asha; Boora, Sukhvir Singh (International Journal of Computer Sciences and Engineering, 2014)
Task scheduling problem can be defined as a method to schedule tasks for execution . Task scheduling in multiprocessor system is also called as multiprocessor scheduling , and is long studied and difficult problems that continues to be a topic of considerable research. Task scheduling in multiprocessor is a term that can defined as finding a schedule for a general task graph to be executed on a multiprocessor system so that execution time can be minimized. Efficient multiprocessor task scheduling is essentially the problem of allocating a set of computational jobs to a set of processors to minimize the overall execution time. This is NP- complete problem that can be solved only by search techniques and heuristic. Genetic algorithm is the best search technique for solving this problem because they are known to provide robust, stochastic solutions for numerous optimization problems .